Polemik Pembangunan PLTU di Kalimantan Utara: Analisis Permasalahan Berdasarkan Prinsip-prinsip Ekologis-Laudato Si dan Filsafat Panteisme Spinoza - Mariano, Andreas; Ranubaya, Fransesco Agnes; Marianta, Yohanes I Wayan (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2025)
Natural resources represent a commodity that is in high demand and is used to meet human needs. One of the natural resources that is in high demand is coal. The development of technologies such as trains, fuel and power plants requires the use of coal. In light of these developments, it is imperative that coal be managed in an environmentally responsible manner to prevent damage to the environment and avoid further environmental pollution. In the preceding one years ago, a case emerged that was brought to public attention. The case in question concerns the construction of a Steam Power Plant (PLTU) in North Kalimantan. The objective of this paper is to examine the case in question with reference to the perspectives set forth in Laudato Si and Baruch Spinoza's philosophy of pantheism. The issue originated with the opposition of various parties to the construction of the infrastructure. The rejection was based on the pretext of preserving the environment. Conversely, the government maintains that electricity supply is necessary for equitable development. Both parties' intentions are commendable and well founded. However, it is crucial to determine which objective is of greater importance and necessity. In light of these challenges, this paper's central inquiry is: What is the primary issue at the core of this controversy? How are the government's efforts to resolve it and the agreement with local residents progressing? This writing employs the literature method and pertinent literature sources. Furthermore, this writing aims to elucidate the necessity of environmental preservation in the context of Laudato Si and Spinoza's philosophy of pantheism regarding nature. Furthermore, the benefits of writing provide suggestions and solutions for the proper resolution of this problem. In light of the aforementioned considerations, the findings of this paper endeavor to integrate the principles of environmental impact assessment (AMDAL) and renewable energy development into a comprehensive framework for ensuring the long term sustainability of the ecosystem and the well being of the people of North Kalimantan. The discussion is structured around four key elements: First, A detailed account of the case in question. Second, A concise biographical sketch of Baruch Spinoza and an overview of his contributions to philosophical thought. Third, An examination of the fundamental principles that underpin the protection of the natural environment. Fourth, A comparative analysis of the principles espoused in Laudato Si and those articulated in Spinoza's pantheistic philosophy